BX795-Organic Acid Coevaporates: Evaluation of Solid-State Characteristics, In Vitro Cytocompatibility and In Vitro Activity against HSV-1 and HSV-2 - Yogesh Sutar; Tejabhiram Yadavalli; Sagar Kumar Paul; Sudipta Mallick; Raghuram Koganti; Harsh Chauhan; Abhijit A. Date; Deepak Shukla (MDPI AG, 2021)
BX795 is a TANK binding kinase-1 inhibitor that has shown excellent therapeutic activity in murine models of genital and ocular herpes infections on topical delivery. Currently, only the BX795 free base and its hydrochloride salt are available commercially. Here, we evaluate the ability of various organic acids suitable for vaginal and/or ocular delivery to form BX795 salts/cocrystals/co-amorphous systems with the aim of facilitating pharmaceutical development of BX795. We characterized BX795-organic acid coevaporates using powder X-ray diffractometry, Fourier-transform infrared spectroscopy (FT-IR), Raman spectroscopy, 1H-nuclear magnetic resonance spectroscopy, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to elucidate the interaction between BX795 and various organic acids such as taurine, maleic acid, fumaric acid, tartaric acid, and citric acid. Furthermore, using human corneal epithelial cells and HeLa cells, we evaluated BX795-organic acid coevaporates for in vitro cytocompatibility and in vitro antiviral activity against herpes simplex virus-type 1 (HSV-1) and type-2 (HSV-2). Our studies indicate that BX795 forms co-amorphous systems with tartaric acid and citric acid. Interestingly, the association of organic acids with BX795 improved its thermal stability. Our in vitro cytocompatibility and in vitro antiviral studies to screen suitable BX795-organic acid coevaporates for further development show that all BX795-organic acid systems, at a concentration equivalent to 10 µM BX795, retained antiviral activity against HSV-1 and HSV-2 but showed differential cytocompatibility. Further, dose-dependent in vitro cytocompatibility and antiviral activity studies on the BX795-fumaric acid system, BX795-tartaric acid co-amorphous system, and BX795-citric acid co-amorphous system show similar antiviral activity against HSV-1 and HSV-2 compared to BX795, whereas only the BX795-citric acid co-amorphous system showed higher in vitro cytocompatibility compared to BX795.